Analysis of the Effect of Islamic Character Education, Multicultural Learning, and Extracurricular Activities on the Character Building of Pesantren Students in Central Java - Meriyati Meriyati; Siminto Siminto; Abdul Wahid (Westscience Press, 2024)
This study explores the influence of Islamic character education, multicultural learning, and extracurricular activities on the character building of students in Islamic boarding schools in Central Java. A quantitative research design was employed, utilizing a survey method to collect data from 150 students. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicated that Islamic character education, multicultural learning, and extracurricular activities all had significant positive impacts on character building, with path coefficients of, respectively. The model explained 52% of the variance in character building. These findings underscore the importance of integrating religious teachings, multicultural perspectives, and extracurricular engagement in educational curricula to foster the holistic development of students. The study offers valuable insights for educators and policymakers in enhancing character education programs within Islamic boarding schools.